The effect of temperature on the charge transport and transient absorption properties of K27 sensitized DSSC - Ocakoglu, Kasim; Yakuphanoğlu, Fahrettin; Durrant, James R.; Icli, Siddik (Elsevier Science Bv, 2008)
The charge transport and transient absorption properties of K27 dye-sensitized solar cell have been investigated. The current-voltage (l-V) characteristics of the solar cell were analyzed by the thermiontic emission theory. The ideality factor, barrier height and series resistance values of the solar cell were determined. The ideality factor higher than unity indicated the presence of non-ideal behavior in current-voltage characteristics at lower voltages. At the higher voltages, the charge transport mechanism for the solar cell is controlled by a space-charge limited current (SCLC) with an exponential distribution of traps. The built potential values are determined from capacitance-voltage plot and were found to be 0.14 and 0.58 V, respectively. The transient absorption data of K27 DSSC device suggest that the fast and slow phases are taking place. While the fast phase corresponds to regeneration of the dye cation by the iodide redox couple, the slow phase correspond!; to the decay of long-lived I-(2) over bar/TiO2 electron absorption. The best conversion efficiency for K27 DSSC was found to be 0.317% under 100 MW/cm(2) (FF = 0.584, Voc = 480 mV, l(sc) = 1.131 mA). The photocurrent results indicate that the photogeneration of charge carriers is a monophotonic process. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: dye-sensitized solar cell; ideality factor; nanocrystalline TiO2